Statistical Quantification for Supporting Geographical Research in Natural Resource Inventory and Evaluation - Sukendra Martha (Forum Geografi, 1999)
In supporting geographical researches, statistical quantifications are required to assist natural resources inventory and evaluation. Statistical analysis for any research either in  sciences will represent the result quality of the research. To do this, all research system implementations. Started from data collection, process to their presentation need to apply quantitative statistics data and numbers. This paper is meant as introducing all geography researchers in conducting researh tasks, particularly in the field natural resources inventory and evaluation.